Method and system for generating a Columnar Tree Map - Armitage, John (2014)
A method and system to generate a columnar tree map of a hierarchical structure is provided. An example system comprises a memory, at least one processor coupled to the memory, a data access module configured to access a hierarchical data structure, and a tree map generator to generate a tree map using at least one processor. The tree map generator generates and renders a tree map for a target data set based on the size and dimensions of a viewing area provided on a target display device, the values associated with categories in the data set, and a predetermined column width.